Evaluating Pakistan's Engagement with the Belt and Road Initiative (BRI) and Build Back Better World (B3W): Present and Future Perspectives - Sanwal Hussain Kharl; Arhama Siddiqa; Saqib Khan Warraich (BTTN Journal)
In contemporary times, the pursuit of a sustainable geoeconomics policy is now a requirement. Launched in 2013, China’s Belt and Road Initiative (BRI) aims to enhance economic integration through substantial infrastructure development. Announced in 2021, G7’s Build Back Better World (B3W) also concentrates on sustainable development, with a special emphasis on health, climate security and gender equality. Pakistan, positioned at a geopolitical crossroad, as well as a vital component of the China-Pakistan Economic Corridor (CPEC), stands to be affected by both BRI and B3W initiatives.  In tandem, both initiatives complement each other. This research will do a comparative analysis of both projects and will use geopolitical realism to understand the various strategic facets and outcomes as well as underscore the broader consequences of BRI and B3W for global development.